Attitude of junior doctors towards needle-stick injuries - Gurung, B; Gurung, U (Journal of Institute of Medicine Nepal, 2010)
Background: Needle-stick injury (NSI) is a known occupational hazard to health care workers. This study is done to estimate the prevalence of needle-stick injuries and evaluate the attitude of junior doctors towards it. Methods: This is a cross sectional study carried out in April 2008. Questionnaires related to NSI were distributed amongst residents, house officers and interns currently working in various departments of Tribhuvan University Teaching Hospital. Data obtained from the completed questionnaires were analyzed with simple manual analysis using frequency and percentage. Results: Hundred twenty four (83.7%) doctors had sustained NSI. Amongst those who sustained NSI, 67 (54%) doctors washed their hands with soap and water or antiseptics, 11 (8.8%) reviewed the patient's serological status, 42(33.8%) did both of the above while 4(3.2%) did nothing. Eighteen (14.5%) doctors reported the incident to hospital authority while 106(85.4%) doctors did not. Thirty six (33.9%) doctors did not report because they did not consider it important; 50(47.1) doctors did not know what to do; 12 (11.3%) thought the hospital was not concerned regarding such injuries and 8(7.5%) did not report as the patients serology was negative. Conclusion: NSI is common amongst junior doctors. Washing hands with soap and water is what most doctors do following NSI. Non-reporting of NSI is high. Awareness of post exposure management following NSI is important to reduce the possible transmission of blood borne pathogens. Key words: needle-stick injuries, Post exposure prophylaxis (PEP), under reporting The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, August, 2009; 31:2 28-31